Postoperative Tinnitus After Vestibular Schwannoma Surgery Depends on Preoperative Tinnitus and Both Pre- and Postoperative Hearing Function - Trakolis, Leonidas; Ebner, Florian H.; Machetanz, Kathrin; Sandritter, Joey; Tatagiba, Marcos; Naros, Georgios (Frontiers in Neurology, 2018)
Objective: Tinnitus is one of the most common symptoms before and/or after the surgical removal of a vestibular schwannoma (VS) affecting almost half of the patients. Although there is increasing evidence for the association of hearing impairment and VS-associated tinnitus, the effect of hearing deterioration due to surgery and its relation to the postoperative tinnitus is poorly investigated. This knowledge, however, might i) enlighten the pathophysiology of VS-associated tinnitus (i.e. peripheral or central origin) and ii) improve preoperative patient counselling. The aim of this study was to understand the predisposition factors for a postoperative tinnitus in relation to hearing outcome after surgery. Methods: This retrospective study analysed the presence of tinnitus in 208 patients with unilateral vestibular schwannoma before and after surgical removal. A binomial logistic regression was performed to ascertain the effect of pre- and postoperative hearing as well as age, gender, tumor side and size, and intraoperative cochlear nerve resection on the likelihood of postoperative VS-associated tinnitus. Results: Preoperative tinnitus was the strongest predictor of postoperative tinnitus. In addition, deterioration of functional hearing was increasing, while functional deafferentation (i.e. postoperative hearing loss) of non-functional hearing was reducing the risk of postoperative tinnitus. At the same time, patients with no preoperative tinnitus but complete hearing loss had the lowest risk to suffer from postoperative tinnitus. Patient age, gender, tumor side and size as well as cochlear nerve resection played a subordinate role. Conclusion: While the presence of preoperative tinnitus was the strongest predictor of postoperative tinnitus, there is a distinct relationship between hearing outcome and postoperative tinnitus depending on the preoperative situation. Functional or anatomical deafferentation due to surgical tumor removal does not prevent postoperative tinnitus per se.